Effect of spark gap shape on time lag. Issue 13 (1st June 2013) - Wan, F.; Pommerenke, D.; Shumiya, H.; Araki, K.
Abstract : Presented is the effect of sharp spark gap on time lag, which is a very important factor in electrostatic discharge modelling. A long time lag induces a large discharge current and a fast rise time. The large discharge current often causes soft errors in many products. Through measurement and simulation, the relation between sharp edge and time lag is quantified. The result can be used in numerical simulation of breakdown voltage. With the numerical simulation, knowing only the geometry of the spark gap can obtain the discharge current.